Dealing with Unexpected Circumstances: Judicial Modification of Contract under Indonesian and Dutch Law - Taufiq Adiyanto (Faculty of Law, Hasanuddin University, 2019)
After the conclusion of a contract, uncontrolled situations of the parties may lead to non-performance of the contract not only in the form of impossibility but also through excessive onerousness. This paper is seeking to compare regulations and cases concerning change of circumstances of the contract under the Indonesian and Dutch legal systems. The aim is to compare a legal remedy when the contract is imbalance and puts other party in burdensome condition to perform. Indonesian law still uses the all-or-nothing approach of termination and rejects the concept of subjective (relative) force majeure to modify a binding contract, although in some cases Indonesian Supreme Court has modified some contracts on the basis good faith principle. Dutch law, on the other hand, has an explicit provision for adjustment of contract on the basis unforeseen circumstances in Article 6:258 DCC. This jurisdiction accepts that unforeseen circumstances can be justified as a basis for adaptation of the contract.